Modeling and prediction of HIV in China: transmission rates structured by infection ages - Yicang Zhou; Yiming Shao; Yuhua Ruan; Jianqing Xu; Zhien Ma; Changlin Mei; Jianhong Wu (Mathematical Biosciences and Engineering)
HIV transmission process involves a long incubation and infectionperiod, and the transmission rate varies greatly with infection stage. Conse-quently, modeling analysis based on the assumption of a constant transmissionrate during the entire infection period yields an inaccurate description of HIVtransmission dynamics and long-term projections. Here we develop a generalframework of mathematical modeling that takes into account this heterogeneityof transmission rate and permits rigorous estimation of important parametersusing a regression analysis of the twenty-year reported HIV infection data inChina. Despite the large variation in this statistical data attributable to theknowledge of HIV, surveillance efforts, and uncertain events, and although thereported data counts individuals who might have been infected many yearsago, our analysis shows that the model structured on infection age can assistus in extracting from this data set very useful information about transmissiontrends and about effectiveness of various control measures.